The place of Political Risk Insurance in the political risk management strategy of multinational corporations - Violeta Iftinchi; Gheorghe Hurduzeu (Romanian Economic Journal, 2016)
Confronted with a variety of political risks that affect their international activities, multinational corporations (MNCs) can use Political Risk Insurance (PRI) as a method to mitigate some of those risks. The aim of this article is to present the main characteristics of the PRI policies and participants, to highlight its benefits and to put forward three limitations that prevent MNCs in using PRI in their political risk management strategy (fluctuating capacity on the market, high premium rates and small compensation value). The recent trend in incorporating corporate social responsibility requirements as a pre-condition for providing PRI can contribute to lowering PRI premium rates.